Utility of Schwann/2E and Sox10 in distinguishing CD57‐negative olfactory groove schwannoma from olfactory ensheathing cell tumor: A case report and review of the literature. Issue 4 (16th April 2020) - Masuda, Hiroyuki; Nemoto, Masaaki; Okonogi, Shinichi; Node, Yasuhiro; Ando, Syunpei; Kondo, Kosuke; Harada, Naoyuki; Sugo, Nobuo
Abstract : We herein report a patient who was diagnosed as having olfactory groove schwannoma (OGS) which was negative for CD57 (Leu7) but positive for Schwann/2E and Sox10. A 13‐year‐old female with a chief complaint of headache was referred to our department due to a tumor lesion in the anterior skull base identified by magnetic resonance imaging (MRI). At the first visit, she did not exhibit altered consciousness, motor palsy, anosmia, seizures, or café au lait spots. On contrast‐enhanced computed tomography (CT), a heterogeneously enhanced tumor, 50 × 45 × 50 mm in size, was observed at the anterior skull base. The left cribriform plate was thinner on bone window CT. The tumor exhibited strong, heterogeneous gadolinium enhancement on MRI as well. Slight tumor staining was observed by angiography of the left internal carotid artery but not the left external carotid artery. The patient was preoperatively diagnosed as having meningioma and underwent gross tumor resection via the basal interhemispheric approach. The tumor was strongly positive for S‐100 protein and negative for epithelial membrane antigen and CD57 by immunostaining. The tumor was positive for both Schwann/2E and Sox10, which aided in the differential diagnosis between OGSs and olfactory ensheathing cell (OEC) tumors, and the definitive diagnosis was OGS. The assessment of immunoreactivities for Schwann/2E and Sox10 might be necessary to differentiate CD57‐negative Schwannomas from OEC tumors.